2017
DOI: 10.1021/acs.jpcc.6b08236
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Benzene on the RuO2(110) Surface

Abstract: Hydrocarbon tribopolymer, a type of polymer formed due to friction between surfaces, is a major impediment to the development of micro-and nanoelectromechanical systems (MEMS/NEMS) devices for industrial application. Tribopolymer buildup can prevent MEMS and NEMS from making or breaking electrical contact. We describe the adsorption of benzene (C 6 H 6 ) on the RuO 2 (110) surface using density functional theory. This adsorption is an important initial step in the mechanism of hydrocarbon tribopolymer layer fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Additionally, the RuO 2 (110) surface is the most common and thermodynamically most stable surface among the RuO 2 surfaces. [75][76][77][78] In the DFT analysis, a seven-layer slab geometry of the most common orientation (110) of RuO 2 surface with a vacuum layer of about 20 Å was chosen, further sandwiched by the semi-infinite vacuum called the effective screening medium (ESM). The modeled system is a continuous layer, about 10 Å in thickness, which represents a nanoscale film, and captures the behavior of nonedge nanocrystal regions, which form the majority of the surface area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the RuO 2 (110) surface is the most common and thermodynamically most stable surface among the RuO 2 surfaces. [75][76][77][78] In the DFT analysis, a seven-layer slab geometry of the most common orientation (110) of RuO 2 surface with a vacuum layer of about 20 Å was chosen, further sandwiched by the semi-infinite vacuum called the effective screening medium (ESM). The modeled system is a continuous layer, about 10 Å in thickness, which represents a nanoscale film, and captures the behavior of nonedge nanocrystal regions, which form the majority of the surface area.…”
Section: Resultsmentioning
confidence: 99%
“…We have chosen the RuO 2 (110) surface in our DFT simulations because the high‐resolution transmission electron microscopy (HRTEM) image of the ncRuO 2 revealed that the RuO 2 (110) is the dominant exposed surface (Figure S11, Supporting Information). Additionally, the RuO 2 (110) surface is the most common and thermodynamically most stable surface among the RuO 2 surfaces . In the DFT analysis, a seven‐layer slab geometry of the most common orientation (110) of RuO 2 surface with a vacuum layer of about 20 Å was chosen, further sandwiched by the semi‐infinite vacuum called the effective screening medium (ESM).…”
Section: Resultsmentioning
confidence: 99%
“…The chosen functional was the PBE exchange correlation GGA functional . This functional is the most commonly used for studying RuO 2 and correctly describes its conducting nature. , ,,,, The D2 Grimme’s dispersion correction was included in all slab calculations since it is essential to properly describe water adsorption and hydrogen bonding . Test calculations with the most recent D3 correction for dispersion were also performed with the aim of analyzing the influence of the Grimme’s parametrization in the adsorption energies and the relative stabilities between the H 2 O and the OH – /H + deprotonated structures.…”
Section: Computational Detailsmentioning
confidence: 99%